The Methods of Information Management in the Space of the Current Scientific Discourse: Recommendations for Public Sector Organisations - Baran, Michał (Journal of Public Governance, 2024)
Objectives: The information age constantly poses new challenges for management specialists. Such a circumstance encourages to creative considerations on how to overcome these challenges. The dynamics of changes taking place in the organisational environment and the response to them, which is formulated by the scientific community, is then an interesting subject of research. The author adopts the thesis that it is possible to identify certain common elements of the ongoing discourse, which determine its current character, adequate to the challenges of the present day. The presented analysis includes a study of examples of invoking information management methods in publications from recent years. Research Design & Methods: The qualitative text analysis – especially one based on the method of binary oppositions – was used in the considerations. The use of this method makes it possible to indicate examples of common denominators connecting the publications that were the subject of the research. Findings: As the result of the conducted research, the dimension of directing the discourse to the context of using the latest IT technologies to improve internal processes and, on the other hand, to increase the scope of interorganisational integration was revealed. Another dimension of the discourse turned out to be the reference to information management methods in the context of using IT to change the role and importance of the human factor, but also to autonomise and automate the production system. Implications / Recommendations: Based on the conducted analyses, recommendations were formulated that will make it easier for public sector organisations to implement their missions within the context of identified dimensions. However, it is necessary to implement changes consistent with the detected trends shaping the interorganisational information exchange network. Contribution / Value Added: It was found out that in the face of the changing level of complexity of the environment and the dynamically growing level of inter-organisational integration, the public sector must ensure its ability to engage in ongoing processes. This requires the introduction of appropriate system and organisational solutions as well as the development of analytical competences, taking into account the potential of artificial intelligence and other advanced information technologies. Article classification: research article JEL classification: D82, M10, M15